(3GdOQ GdfKjQ JdNjU GHf GdCKjQ aj ZQjH GdMOjKs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s; (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO GHf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CfYe gPG eDda dNUJ ajg cJGH GdfgGjI ai ZQjH GdMOjK MQa GdgeRI s
(3BNQgG (B:s
(3jHYJ HaJM GdjGA GdChdi hVe GdYjf GdegedI BNQ GdcJGH s
(3HChdgG Jedcs
(3HgG fXGe GdJYbjHIs
(3HBNQg UaMI hGMOI ef cJGH GdJPjjd hGdJPfjH Ydi fgGjI GdZQjH JCdja GdSjhWis
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs